FTIR and Raman analysis of l -cysteine ethyl ester HCl interaction with dipalmitoylphosphatidylcholine in anhydrous and hydrated states - Arias, Juan Marcelo (2015)
Interactions of l‐cysteine ethyl ester hydrochloride (CE), a bioactive cysteine derivative, with dipalmitoylphosphatidylcholine (DPPC) were investigated. To gain a deeper insight into analyzing l‐cysteine ethyl ester HCl interaction with liposomes of DPPC in anhydrous and hydrated states, we performed experimental studies by infrared (Fourier transform infrared spectroscopy) and Raman spectroscopies. The results revealed that the interaction of CE with the phospholipid head groups was the same in absence or presence of water. In both states, the wavenumber of the PO2− group and CN bond of the choline group decreased. This behavior can be ascribed to the replacement of hydration water and binding to the phosphate group. In the Raman spectrum results for the anhydrous and gel states, the SH stretching band of the CE shifted to lower frequencies with a decrease in its force constant. Biologically active lipophilic molecules such as CE should be studied in terms of their interaction with lipid bilayers prior to the development of advanced lipid carrier systems such as liposomes. The results of these studies provide information on membrane integrity and physicochemical properties that are essential for the rational design of lipidic drug delivery systems.